A Comparison of Higher-Order Weak Numerical Schemes for Stopped Stochastic Differential Equations. (31st August 2016) - Bernal, Francisco; Acebróon, Juan A.
Abstract: We review, implement, and compare numerical integration schemes for spatially bounded diffusions stopped at the boundary which possess a convergence rate of the discretization error with respect to the timestep h higher than . We address specific implementation issues of the most general-purpose of such schemes. They have been coded into a single Matlab program and compared, according to their accuracy and computational cost, on a wide range of problems in up to ℝ 48 . The paper is self-contained and the code will be made freely downloadable.